Differences in Esophageal Cancer Surgery in Terms of Surgical Approach and Extent of Lymphadenectomy: Findings of an International Survey - van Rijswijk, A. S. (Ann Surg Oncol, 2019)
INTRODUCTION: Esophagectomy and lymphadenectomy are essential parts of the multimodal treatment of esophageal carcinoma with curative intent. Treatment regimens vary globally and are subject to debate. A global survey was designed to gain insight into current practice. METHODS: Fifty-seven international expert upper gastrointestinal surgeons received a personal invitation to participate in the survey, which focused on demographics and experience; extent of lymphadenectomy in adeno and squamous cell carcinoma; use of classification systems; neoadjuvant therapy; surgical approach; and specimen handling. RESULTS: The response rate was 88% (50/57 surgeons), with a mean age of 51.6 years and a median number of 15 years of experience in esophageal surgery. The variety in the extent of lymphadenectomy in proximal, middle and distal squamous cell carcinoma, and Siewert I, II and III adenocarcinoma, was considerable. The number of different combinations of lymph node (LN) stations that were resected in the same tumor was high, while the number of surgeons who removed the exact same combination of LN stations was low. Illustrative is Siewert I adenocarcinoma, in which 27 unique combinations of LN stations were resected, with a maximum of two surgeons performing the exact same dissection. Use of neoadjuvant therapy, surgical approach, and specimen handling also show great variety among participants. CONCLUSION: There is no uniform, worldwide strategy for surgical treatment of esophageal cancer. The extent of lymphadenectomy shows great variation for both histologic types. An international observational study is needed to provide evidence on the distribution pattern of lymph node metastases in esophageal cancer and the necessary extent of lymphadenectomy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1245/s10434-019-07316-9) contains supplementary material, which is available to authorized users.